The Diversity of European Research Evaluation Systems - Ochsner, Michael; Kulczycki, Emanuel; Gedutis, Aldis (My University, 2018)
Universities have undergone profound changes in the last decades. A shift towards more accountability and to “new public management” practices in the administration of universities took place and led to an increase of the share of project funds in some countries and to the introduction of performance-based funding systems (PRFSs) in others. In all countries, research evaluation’s importance increases. However, while research evaluation is centralized in some countries, evaluation is organized at the institutional level only in others. Thus, the importance of research evaluation and how it is organised varies across countries. In this paper, we present a typology of national research evaluation systems in Europe that sheds light on the complex issue of national differences in the organisation of research evaluation. We use the data of a two-round Delphi survey among specialists in research evaluation as a basis of our analysis and apply Multiple Correspondence Analysis to create a typology of European research evaluation systems that includes a broad range of countries, including countries, for which not much information is available to the English-speaking research community and takes into account that during the last years also the SSH are more concerned with evaluations but the commonly applied evaluation instruments do not fit their research practices. We identify five types of research evaluation: “non-metric, non-SSH” (with Iceland as the best representor), “non-metric, SSH-specific” (Switzerland, “funding, non-metric” (Norway), “funding, metric” (Denmark) and “metric, English” (Estonia). The main result of this analysis is that the national organization of research evaluation system is a complex issue and the research evaluation landscape in Europe is diverse. Yet some components can be identified that define main types of research evaluation. A secondary result is that different types of research evaluation are linked to different conditions in countries. We therefore recommend, that designers of evaluation systems make a conscious link between the goals to achieve, the incentives to promote and the design of the evaluation system, rather than to strive to the unification of evaluation systems.